ANALISIS SIKAP SOSIAL PADA SISWA KELAS TINGGI MADRASAH IBTIDAIYAH ANWARUL MUSTOFA KECAMATAN KUBU TAHUN 2020 - Imbriti Imbriti; Yuline Yuline; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study contains the Analysis of Social Attitudes in High Class Students of Madrasah Ibtidaiyah Anwarul Mustofa Kacamatan Kubu.2017 / 2018. A common problem in this study is "What is the social attitude of students in Madrasah Ibtidaiyah Anwarul Mustofa Kacamatan Kubu. In particular. 1. What is the attitude of working together with high school students at the Madrasah Ibtidaiyah Anwarul Mustofa Kacamatan Kubu? 2. How to pay attention to the rights of others in high school students of Madrasah Ibtidaiyah Anwarul Mustofa Kubu? 3. What is the attitude of concern for others in high school students at Madrasah Ibtidaiyah Anwarul Mustofa camp? The method used is descriptive method in the form of survey research studies. The sample of this study was 30 students at MI Anwarul Kacamatan Kubu. ? " This study uses a quantitative approach. The data collection technique of this research is the indirect communication technique with a data collection tool in the form of a questionnaire and documentary study technique with a document data collection tool. The data analysis technique uses percentage calculation. Based on the results of data analysis social attitudes of students at MI Anwarul Mustofa Kacamatan Kubu as a whole reached 77.04% with the category "Good".  Keywords: Socia. Attitude.  High Class Students.